Workload, Work Environment, and Employee Performance: The Mediating Role of Public Service Motivation - Maida Nur Khasanah; Farikha Amillahaq (LPPM STIE KRAKATAU, 2025)
The purpose of this study is to determine the effect of Workload and Work Environment on employee performance through public service motivation as an intervening variable at RSUD dr. Gondo Suwarno Ungaran. This study uses a quantitative method because it discusses the relationship between variables using a questionnaire. The sample used in this study was 90 respondents who were distributed to employees of RSUD dr. Gondo Suwarno Ungaran. The data processing technique used in this study uses the software method (SPSS) Statistical Package for Social Science. This study uses descriptive analysis methods, instrument tests, classical assumption tests, hypothesis tests, and Sobel tests. The results of this study indicate that Workload and Work Environment influence Employee Performance. In addition, Public Service Motivation does not act as a mediator on Employee Performance. This study is expected to be useful for the science of HR management and practically also useful for improving performance at RSUD dr. Gondo Suwarno Ungaran..